Racing to Justice : Transforming Our Conceptions of Self and Other to Build an Inclusive Society - Powell, John A. (John Anthony) (Book collections on Project MUSE., 2012)
Renowned social justice advocate John A. Powell persuasively argues that we have not achieved a post-racial society and that there is much work to do to redeem the American promise of inclusive democracy. Culled from a decade of writing about social justice and spirituality, these meditations on race, identity, and social policy provide an outline for laying claim to our shared humanity and a way toward healing ourselves and securing our future. Racing to Justice challenges us to replace attitudes and institutions that promote and perpetuate social suffering with those that foster relationships and a way of being that transcends disconnection and separation.